The Activity Of Students in Study Club Activities Towards Their Qur'an Reading Ability in the Al-Mawaddah Area - Fathor Rozi; Arifia Zhebi Nurdiani (Kartika: Jurnal Studi Keislaman, 2026)
This study examines the effect of student activeness in Study Club activities on their Qur'anic reading ability at the Al Mawaddah area of Nurul Jadid Islamic Boarding School. Motivated by persistent disparities in reading skills and low engagement in non-formal learning, this research employs a qualitative case study approach with data collection through in-depth interviews, participant observation, and documentation. The findings reveal that active participation in Study Clubs significantly enhances students' self-awareness in identifying and correcting reading errors, fosters reflective attitudes and personal responsibility for learning, and strengthens self-confidence that transfers to formal classroom contexts. The Study Club functions as a collaborative, non-pressuring space that enables intensive practice, immediate peer feedback, and the internalization of quality standards for Qur'anic recitation. This study concludes that non-formal learning activities based on student activeness can serve as an effective alternative model for improving Qur'anic learning quality in Islamic boarding schools. Theoretically, it shifts the focus from teaching methods to student engagement, while practically, it recommends integrating structured Study Clubs into the formal curriculum